Platform of Citizen Interaction: the contribution to the governability of New TIC´s and Citizen Relational Management - Doberti, Juan (2016)
Understanding "governability" as an interaction process among government and society, the New Technologies of Information and Communications (NTICs) can contribute as a strategy of improvement and conversion in the type of communication between both actors. This article introduces concepts referred to Customer Relationship Management applications turned into Citizen Relationship Management tools. The plus of a modeling of the multiplatforms functionalities that this solution offers and a protocol of implementation and system migration is a step forward in the achievement of obtaining an electronic government with civil democratic interaction and transparency in the management. The idea of a Platform of Citizen Interaction that auspice as a repository of the communication between public and civil entities allows having a unique and centralized database capable of being segmented of different ways to attend to a great diversity of subject matters.